ANALYSIS OF HIGH RESOLUTION AEROMAGNETIC DATA OF SOME PARTS OF BENUE TROUGH, NIGERIA - Usman, Nuraddeen; Jibril, Ibrahim (FUDMA Journal of Sciences, 2020)
This work is aimed to determine the depth to basement of some magnetic sources in the study area. Four aeromagnetic sheets were acquired from the Nigerian Geological Survey Agency which includes (Bajoga, 131, Gulani, 132, Gombe, 152 and Wuyo, 153). The study area covers an estimated area of about 12100km2 between latitude 90N-110N and longitude 110E-130E. The total magnetic field of the study area have been evaluated. In order to determine the basement depth, spectral analysis technique was applied. Detailed analysis of the aeromagnetic data for the study area was performed. The procedure involved in the analysis include reduction to equator to remove the effect of inclination, contouring of the total magnetic intensity, separation of the regional and residual anomalies using polynomial fitting of first order, qualitative interpretation and quantitative interpretation. The residual field of the study area composes of low magnetic anomalies reaching a minimum value of -158.6nT as observed in the northern and southern parts and high magnetic anomalies reaching a maximum value of 178.1nT as observed in the western part of the study area. The result from the spectral analysis for each block shows that the depths to the magnetic source are 5.20Km for block 1, 5.74Km for block 2, 7.59Km for block 3 and 3.56Km for block 4. The average depth to magnetic source in the study area was found to be 5.52Km. Based on the computed average sedimentary thickness obtained in this study area, hydrocarbon accumulation in the study area is feasible.